Art and life: the nineties in Buenos Aires - Lemus, Francisco (Revista do Colóquio, 2024)
Through a series of discussions, articles of art, and cultural experiences that took place in Buenos Aires during the 1990s, this article focuses on the aesthetic and micropolitical relationships that highlight the emergence of HIV/AIDS. It centers on the development of the Visual Arts Gallery at the Centro Cultural Rojas and the different forms of survival and resistance generated around the epidemic. Article originally published as LEMUS, F.. Arte y vida. Los años noventa en Buenos Aires. Heterotopías, n. 4, v. 7, 30 jun. 2021, pp. 1–25. Disponível em: https://revistas.unc.edu.ar/index.php/heterotopias/article/view/33426.
Keywords: argentinian contemporary art; micropolitics; hiv/aids